The Politicization of Religion and Law Enforcement in Indonesia's Democratic Elections: An Islamic Legal Perspective - Qosim, M. Rizal; Hariz, Hajar Salamah Salsabila; Arowosaiye, Yusuf Ibrahim; Azizah, Mabarroh; Idamatussilmi (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
The politicization of religion in Indonesia's democratic elections represents a structural challenge that disrupts constitutional governance, weakens legal neutrality, and conflicts with the normative principles articulated in al-Māwardī's fiqh siyāsah dustūriyyah. While existing scholarship has addressed the interplay between religion and politics, few studies examine how the strategic manipulation of religious symbols and clerical authority erodes institutional integrity when analysed through al-Māwardī's framework of governance. This study investigates the mechanisms and consequences of religious politicization by integrating key concepts of al-Māwardī, such as ʿadl (justice), amānah (trust), wilāyah al-qaḍā' (judicial authority), and ḥisbah (public oversight) as constitutional ethical standards for political conduct. Utilising a qualitative descriptive method and case study approach, the research analyses interactions among political elites, religious actors, and law enforcement bodies to understand how these relationships influence decision-making processes. The findings reveal three constitutional distortions: the instrumentalisation of religious narratives to delegitimise political opponents; the intervention of religious groups in judicial processes that threaten the independence of legal institutions; and transactional alliances that compromise the objectivity of state authority. From the perspective of al-Māwardī's fiqh siyāsah, these practices violate maqāṣid al-sharīʿah, especially the preservation of justice, intellect, and social cohesion, and contradict the constitutional ethics expected of legitimate governance. This study concludes that religious politicization functions as a systemic threat to the rule of law, undermines public trust, and deviates from al-Māwardī's normative model of just political authority. The research contributes a jurisprudential framework demonstrating how fiqh siyāsah dustūriyyah can guide ethical and accountable governance in contemporary Muslim-majority political systems.